Design and Simulation of Multiple Elements for Rectangular and Circular Antenna Arrays - Hazila Othman (School of Computer and Communication Engineering, 2012)
The scope of this thesis is to understand the concept of microstrip patch antenna, corporate feeding technique, and application of microstrip patch antenna